2020
DOI: 10.1002/sctm.20-0118
|View full text |Cite
|
Sign up to set email alerts
|

Potential of mesenchymal stem cells as topical immunomodulatory cell therapies for ocular surface inflammatory disorders

Abstract: Ocular surface inflammatory disorders (OSIDs) are a group of highly prevalent, heterogeneous diseases which display a variety of aetiologies and symptoms and are risk factors for serious complications including ocular and cornea impairment. Corneal inflammation is a common factor of all OSIDs, regardless of their cause or symptoms. Current medications include over-the-counter lubricating eye drops, corticosteroids, and ciclosporin, which either do not treat the corneal inflammation or have been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 107 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Although HCEnC therapy was used as a point of reference for discussion, many of the underpinning principles and challenges are applicable to the broader development of other cell therapies such as those derived from hematopoietic cells, MSCs, lymphocytes, and dendritic cells, among others. 95,96 While harmonizing the regulatory framework across different regions would be challenging, a clear overview on the similarity and disparity of different regional frameworks would facilitate the navigation and development of CTPs from bench to bedside for the academics, industrial partners, and relevant stakeholders.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Although HCEnC therapy was used as a point of reference for discussion, many of the underpinning principles and challenges are applicable to the broader development of other cell therapies such as those derived from hematopoietic cells, MSCs, lymphocytes, and dendritic cells, among others. 95,96 While harmonizing the regulatory framework across different regions would be challenging, a clear overview on the similarity and disparity of different regional frameworks would facilitate the navigation and development of CTPs from bench to bedside for the academics, industrial partners, and relevant stakeholders.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Corneal neovascularization can occur when there is an imbalance between proangiogenic and antiangiogenic factors which there are excessive pro-angiogenic factors such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and matrix metalloproteinase (MMP), while there is a deficiency of anti-angiogenic factors such as pigment epithelium-derived factor, angiostatin, endostatin and thrombospondin. MSC inhibit corneal neovascularization by downregulating pro-angiogenic factors (VEGF, MMP) and upregulating anti-angiogenic factors (TSP-1, PEDF, sLFT-1, TSG-6) (Beeken et al, 2020;Eslani et al, 2017;Oh et al, 2008;Ghazaryan et al, 2016;Komaratih et al, 2019;Song et al, 2018;Yao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cell secretome has been investigated to have the role as an antiinflammatory, anti-angiogenesis, and immunomodulatory. Several studies have shown that MSC not only reduces inflammation and reduces corneal opacity, but can also significantly inhibits neovascularization in corneal chemical injury (Almaliotis et al, 2015;Cejka et al, 2016;Beeken et al, 2020;Ke et al, 2015;Ma et al, 2006;Pawitan, 2014). The aim of this study is to analyze the effect of limbal mesenchymal stem cell (L-MSC) secretome in inhibition of corneal neovascularization in an animal model of alkali chemical injury by evaluating corneal neovascularization clinically and histopathologically.…”
Section: Introductionmentioning
confidence: 99%
“…They possess powerful self-renewal ability and multilineage differentiation potential via symmetric/asymmetric cell division [3][4][5]. Currently, MSC-based therapy has been diffusely exploited in the treatment of numerous diseases in basic science and clinical medicine [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%